Alternatif Peningkatan Ekonomi Masyarakat Melalui Inovasi Produk Olahan Singkong Menjadi Kudapan Hipnotis Colourfull Di Desa Pasar Pedati Kabupaten Bengkulu Tengah - Maryanti, Joko Saputra; Yusdayanti, Nirta Pera; Az-Zahra, Putri; Arif, Hilda Meisya; Fariadi, Herri (Jurnal Dehasen Mengabdi, 2024)
The Student Community Service was carried out in Pasar Pedati Village, Central Bengkulu Regency, to be precise in Hamlet 2 because there are still many people who plant cassava. For the marketing of cassava itself there it is relatively unstable, sometimes it goes up and down according to consumer demand and there are also places where cassava plants are processed into flour but they also experience problems for marketing, therefore to help improve the economy of our society we make innovations in processed food made from cassava so that the community can directly make processed cakes from cassava so that in this way the community can process cassava crops and sell processed cakes to help the economy. Student community service activities aim to provide knowledge to the community about cassava processing and practice how to make Colorful Hypnotic snacks.The settlement method is by making cassava into snacks. This student community service activity (PMM) from the Pasar Pedati Village officials gave appreciation for wanting to visit and choosing Pasar Pedati Village as a place for student community service to share knowledge, and have held direct practice on how how to make this colorful hypnotic cake. After that there was a presentation represented by one of the village officials he hoped that this activity would not only end here but could establish friendship so that when there were people experiencing difficulties or problems in processing or marketing cassava they could work together whether there was a bazaar or other activities.